Single cell deformability cytometry using microfluidics - Low, Xavier Jun Wei (Nanyang Technological University, 2020)
The changes in cellular mechanical properties are linked to several biological activities such as cell differentiation, cell proliferation and disease development. Conventional biomechanical tools are slow (~10 cells/hr) and laborious, which advocates a critical need for novel tools enabling high throughput single-cell mechanophenotyping. In this thesis, we report a novel microfluidic deformability cytometer which compasses the use of hydropipetting technique with viscoelastic fluid to induce cell deformation in a rapid and precise manner. The microchannel design consists of inertial-based asymmetric flow focusers and two cross junctions where fluid siphoning and hydropipetting occur continuously to induce flow-induced cell stretching and compression, respectively. As a proof of concept, polydimethylsiloxane (PDMS) microparticles of different stiffness were used to evaluate the sensitivity of the device. We first optimized the fabrication method (surfactant, vortex timing), and characterize particle size and yield using 2 different PDMS formulations (PDMS 184, PDMS 527). Next, we tested the deformability cytometer using the fabricated PDMS particles and showed that we can distinguish them based on deformability index. Finally, bladder carcinoma (HTB9) cells treated with and without paraformaldehyde (PFA) (a cell fixing agent) were tested, and significant morphological differences were observed on the stiffer PFA-treated HTB9 cells. Taken together, the results demonstrated the developed technology is high throughput (100 cells/sec) with a large dynamic range of cell stiffness (5.0 kPa to 1.7 MPa), and can be further developed as a label-free single cell technique for rapid and point-of-care diagnostics.